10-3t=-7t-10

Simple and best practice solution for 10-3t=-7t-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-3t=-7t-10 equation:



10-3t=-7t-10
We move all terms to the left:
10-3t-(-7t-10)=0
We get rid of parentheses
-3t+7t+10+10=0
We add all the numbers together, and all the variables
4t+20=0
We move all terms containing t to the left, all other terms to the right
4t=-20
t=-20/4
t=-5

See similar equations:

| 7a-22=180 | | 3(4a+2)=2(a−2)= | | 10+8w=6w-10+4 | | –7+–4y=61 | | -10(x-2)-16=42 | | -6+7w=6w | | `5x+2x-9=40` | | 6x9=72 | | 72x+36x^2=0 | | 4*5^(x)=100 | | 4a+9-a-11=-17 | | 7x+35=3(5x-7) | | 3(2x+5)=110 | | 10x-2=-3+8x | | x=(50+50-25)*0+2+2 | | 1/3c=3/8=31/2 | | 10-3p=-8-6p | | 3(8+4x)=48 | | 2(k+1)=14 | | -7(2x+3)=-14-14 | | 9x-3x-4=-42 | | 2+–3u=11.9 | | x=(50+50-25*0)+2+2 | | 1/(3x+15)-2/3x=1/(x+5) | | 1b=14 | | C(x)=50x+20 | | -3-8(4n-3)=-2n-39 | | -p=-3p-2 | | x=50+50-25*0+2+2 | | E=-2.4t+75E | | 2(1-7)a=38-2a | | 3q-5=-14 |

Equations solver categories